An Important Role of Blood and Lymphatic Vessels in Inflammation and Allergy. (31st January 2013) - Zgraggen, Silvana; Ochsenbein, Alexandra M.; Detmar, Michael
Abstract : Angiogenesis and lymphangiogenesis, the growth of new vessels from preexisting ones, have received increasing interest due to their role in tumor growth and metastatic spread. However, vascular remodeling, associated with vascular hyperpermeability, is also a key feature of many chronic inflammatory diseases including asthma, atopic dermatitis, psoriasis, and rheumatoid arthritis. The major drivers of angiogenesis and lymphangiogenesis are vascular endothelial growth factor- (VEGF-)A and VEGF-C, activating specific VEGF receptors on the lymphatic and blood vascular endothelium. Recent experimental studies found potent anti-inflammatory responses after targeted inhibition of activated blood vessels in models of chronic inflammatory diseases. Importantly, our recent results indicate that specific activation of lymphatic vessels reduces both acute and chronic skin inflammation. Thus, antiangiogenic and prolymphangiogenic therapies might represent a new approach to treat chronic inflammatory disorders, including those due to chronic allergic inflammation.